Post-traumatic Left Ventricular Aneurysm with Massive Hemopericardium in a Child Presenting 3 Years After a Fall - Wei-Ting Lai; Shan-Miao Lin; Shyr-Jao Wu; Haw-Kwei Hwang; Chun-Chih Peng; Ming-Ren Chen (Elsevier, 2013)
A 7-year-old boy developed a left ventricular aneurysm with massive hemopericardium 3 years ago due to a fall from a fourth-floor window. He had mild neurological sequelae including cranial nerve III palsy and abnormal electroencephalography findings at that time. He had no chest pain until recently when he presented with chest tightness and abdominal pain for 2 days prior to admission. Chest X-ray showed marked cardiomegaly. Echocardiography revealed massive pericardial effusion and a large left ventricular aneurysm. The massive hemopericardium was surgically drained, and the aneurysm was resected under cardiopulmonary bypass. He was discharged uneventfully 1 week after operation. Because symptoms and signs can vary in patients with ventricular aneurysm, we strongly suggest a close clinical follow-up, preferably with chest X-ray or echocardiography, for patients experiencing a blunt chest trauma.